SOME ASPECTS REGARDING IDENTIFICATION OF INTEGRATED MANAGEMENT SYSTEM PROCESSES - Constanta RĂDULESCU; Liviu CÎRȚÎNĂ Marius (Fiabilitate şi Durabilitate)
This paper emphasizes the importance of identifying the necessary processes of the Integrated Management System within an organization .The method that is used to identify management processes, basic processes and support processes is a method known as SIPOC method. Elaboration and documentation of the integrated management system assumes synergic valorisation of the three systems of requirements described in the applicable reference documents.